PEMANFAATAN PATI, TEPUNG, DAN SERAT UBI JALAR ORANGE DALAM PEMBUATAN ROTI KAYA SERAT - Aprilia Simamora; Elisa Julianti; Hotnida Sinaga (Agroindustrial Technology, University of Trunojoyo Madura, 2020)
The orange fleshed sweet potatoes were used to produce flour, starch and the starch residue as fiber sources. This study was conducted to evaluate the effect of the partially substitution of orange fleshed sweet potato flour, starch, residue starch) in bread to the moisture content, ash content, specific volume, color parameter and sensory evaluation. This research used non factorial Completely Randomized Design i.e formulation of orange fleshed sweet potato flour, starch and residue in 15 %, 30 % , 45 % , and 60% substitution. The formulation of sweet potato flour, starch and residue increases significantly higher (p0,01) moisture, ash and crude fibre content. The moisture content of bread in this study were 36,161%; 37,243%; 38,047%; 39,924% and the ash content of this bread were 1,08%; 1,16%; 1,21%; 1,32% for F1, F2, F3, F4, respectively. The lightness, hue, specific volume, hedonic color, taste, texture and general acceptance of this bread that resulted in this study were significantly higher (p 0,01) and the aroma was significantly (p 0,05) reduced, but increased the moisture, ash, crude fibre content, a and b values by the increment of sweet potato flour, starch, and residue. The formulation of composite flours consists of orange sweet potato flour, starch and residue starch can be influence the moisture, ash content, color parameter, specific volume and sensory evaluation of the bread.